Patient Tales : Case Histories and the Uses of Narrative in Psychiarty - Berkenkotter, Carol (Book collections on Project MUSE., 2008)
This text looks into communicating psychiatric patient histories, from the asylum years to the clinics of modern day. In this study of tales of mental illness, Carol Berkenkotter examines the evolving role of case history narratives in the growth of psychiatry as a medical profession.